High-sensitivity integrated detector with nanostructured hydrogel electrode for ascorbic acid determination - Jiang, Shuyue; Zhang, Haifeng; Li, Zhaoxin; Chen, Liang; Liu, Xiaowei (Microchemical journal, 2023)
[Display omitted] •A novel integrated electrochemical detector applied in miniaturized detection instrument was proposed.•Nanostructured hydrogel electrode can effectively improve the durability and reliability of detector.•The detector can output the milliampere current of level, making it easier than other detectors for data analysis.•The sensitivity of this detector for ascorbic acid detection is 161.46 mA·μM−1·cm−2. This paper proposed a novel integrated detector with nanostructured hydrogel electrode (IDNHE) for ascorbic acid detection. The electrochemical detector was integrated on printed circuit board (PCB). The IDNHE employed the nanostructured multi-walled carbon nanotubes/polyaniline/polyvinyl alcohol (MWCNTs/PANI/PVA) hydrogel as the working electrode. The PVA hydrogel can not only effectively combine the PANI and substrate through hydrogen bonds, but also greatly improve the stability and durability of the detector. MWCNTs were used to fabricate the nanostructures, increasing the surface area of electrode. The detection mechanism is based on the redox reaction of PANI with ascorbic acid. The detection limit and the sensitivity of IDNHE were 0.9 μM (S/N = 3) and 161.46 mA·μM−1·cm−2, respectively. Moreover, IDNHE has a satisfactory reproducibility (RSD = 1.43 %), repeatability (RSD = 2.35 %) and long-term stability for 90 days. Therefore, this work undoubtedly provides a considerate choice for the lab on a chip, and further a promising application prospect for developing the portable real-time monitoring device.